A New Report on Mycosynthesis of Silver Nanoparticles by Fusarium culmorum - Bawaskar, Manisha; Gaikwad, Swapnil; Ingle, Avinash; Rathod, Dnyaneshwar; Gade, Aniket; Duran, Nelson; D. Marcato, Priscyla; Rai, Mahendra (Current Nanoscience, 2010)
Plant pathogenic fungus Fusarium culmorum (MTCC-2090) assists in the mycosynthesis of silver nanoparticles. Formation of spherical silver nanoparticles was confirmed from TEM analysis and found in the range of 5-25 nm with an average diameter of 11 nm. Different temperature and pH affects the synthesis of silver nanoparticles indicating that synthesis depends significantly on temperature and pH. Formation of silver nanoparticles at room temperature and pH-7 was found to be optimum for synthesis process. The combined effects of mycosynthesized silver nanoparticles with different antibiotics like kanamycin, erythromycin, oxacillin, tetracycline, vancomycin and gentamycin against Klebsiella pneumoniae (MTCC-7407) and Enterobacter aerogenes (MTCC-6804) were carried out. Oxacillin showed the maximum increase in fold area as compared to other antibiotics tested against both the test organisms. Fungal proteins are responsible for the synthesis of silver nanoparticles. This process is easy, eco-friendly and scalable for the large scale synthesis of silver nanoparticles. The synthesis of silver nanoparticles by F. culmorum has not been reported in the past, and thus, it is being reported for the first time.
Keywords: mycosynthesis